2018
DOI: 10.1002/ijc.31989
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of herd effects among women and heterosexual men after girls‐only HPV16/18 vaccination in the Netherlands: A repeated cross‐sectional study

Abstract: Data on the impact of human papillomavirus (HPV) vaccination on the population HPV prevalence are largely obtained from women. We assessed the impact of the girls‐only HPV16/18 vaccination program in the Netherlands that started in 2009, on trends in HPV prevalence among women and heterosexual men, using data from the PASSYON study. In this cross‐sectional study, the HPV prevalence among 16‐ to 24‐year‐old visitors to sexually transmitted infection clinics was assessed in 2009, 2011, 2013, and 2015. We compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…For women, this is partly explained by an increased proportion of vaccinated women over time who benefit from direct protection of HPV-16/18 vaccination. In a previous analysis with data up to 6 years postvaccination, we reported that heterosexual men already benefited indirectly from this through herd protection [ 10 ]. This finding is reiterated in the current analyses with data up to 8 years postvaccination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For women, this is partly explained by an increased proportion of vaccinated women over time who benefit from direct protection of HPV-16/18 vaccination. In a previous analysis with data up to 6 years postvaccination, we reported that heterosexual men already benefited indirectly from this through herd protection [ 10 ]. This finding is reiterated in the current analyses with data up to 8 years postvaccination.…”
Section: Discussionmentioning
confidence: 99%
“…For this updated analysis, we used data from the PASSYON (Papillomavirus Surveillance Among STI Clinic Youngsters in the Netherlands) study: a biennial cross-sectional survey to assess HPV prevalence among young visitors to SHCs [ 10 ]. In the Netherlands, SHCs offer sexually transmitted infection (STI) testing to those with increased risk, including individuals ≤24 years of age.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding, counterintuitive at first sight, stems from the high burden of cervical cancer compared with other HPV-related cancers and from the notion that herd effects from vaccinating one sex are generally stronger in the opposite sex (10,31,33). The last also explains the strong impact of girls’ vaccination on vaccine-preventable HPV infections in heterosexual men (34,35).…”
mentioning
confidence: 99%